Cold active lipases: biocatalytic tools for greener technology - Mhetras, Nutan; Mapare, Vidhyashri; Gokhale, Digambar (Applied Biochemistry and Biotechnology, 2021)
Lipases are enzymes that catalyze the ester bond hydrolysis in triglycerides with the release of fatty acids, mono- and diglycerides, and glycerol. The microbial lipases account for \$400 million market size in 2017 and it is expected to reach \$590 million by 2023. Many biotechnological processes are expedited at high temperatures and hence much research is dealt with thermostable enzymes. Cold active lipases are now gaining importance in the detergent, synthesis of chiral intermediates and frail/fragile compounds, and food and pharmaceutical industries. In addition, they consume less energy since they are active at low temperatures. These cold active lipases have not been commercially exploited so far compared to mesophilic and thermophilc lipases. Cold active lipases are distributed in microbes found at low temperatures. Only a few microbes were studied for the production of these enzymes. These cold-adapted enzymes show increased flexibility of their structures in response to freezing effect of the cold habitats. This review presents an update on cold-active lipases from microbial sources along with some structural features justifying high enzyme activity at low temperature. In addition, recent achievements on their use in various industries will also be discussed.
Keywords: Cold active lipases; Frail compounds; Psychrophilic microbes; Synthesis of chiral molecules